Peran Guru Dalam Penguatan Pendidikan Karakter - Benediktus Denar (Jurnal Alternatif Wacana Ilmiah Interkultural, 2019)
This paper intends to describe the importance of character education as a more holistic model of education to reach a generation with integral personalities. The concept of character education confirms that education not only covers with cognitive aspects, but also with spiritual (spiritual and emotional development) aspects, sports and kinesthetic (physical and kinesthetic development) aspects, and aspects of affection and creativity. Character education can be implemented through learning activities, routine activities, exemplary, conditioning, and in various activities at home and society.